Can wheatears weather the Atlantic? Modeling nonstop trans-Atlantic flights of a small migratory songbird. (2nd July 2014) - Bulte, Marc; McLaren, James D.; Bairlein, Franz; Bouten, Willem; Schmaljohann, Heiko; Shamoun-Baranes, Judy
Abstract: Oceans represent extreme ecological barriers for land birds. Yet the Northern Wheatear ( Oenanthe oenanthe leucorhoa ), a 25-g songbird, negotiates the North Atlantic Ocean twice yearly between Canadian natal and sub-Saharan wintering grounds. Each autumn, these migrants appear to have 2 options: (1) a detour via Greenland, Iceland, and/or Europe to reduce the extent of open-ocean flights or (2) an astonishing nonstop flight of 4, 000–5, 000 km without resting opportunities between eastern Canada and northwestern Africa. We assessed the feasibility and reliability of nonstop trans-Atlantic migration of Northern Wheatears from Canada to Africa using an individual-based model incorporating flight costs and autumnal wind data from 1979 to 2011. Prevalent wind conditions were supportive of nonstop migration, especially at high altitudes and when winds at departure were favorable. For modeled individuals with high fuel loads, flying at altitudes of ∼3, 000 m, successful nonstop trans-Atlantic flights reached Africa on 62% of departure days. On 24% of unsuccessful departure days, individuals could have first stopped in Europe before continuing to Africa. Durations of successful flights varied between 31 and 68 hr, with significantly shorter flights after mid-September. It remains unclear whether natural selection might favor nonstop ocean crossings by O. o. leucorhoa between North America and Africa, but we conclude that reliably supportive winds en route and potentially huge time savings render it a feasible migration strategy.